Fractura aislada de sacro en la edad pediátrica - César Cabrera; Viviana Teske (Anales de la Facultad de Medicina, 2016)
Fractures of the pelvis generally make up between 1% and 3% of all the fractures at a pediatric age. Sacral fractures are the least common among fractures of the pelvis. In spite of this, this type of fracture has to be carefully attended since it may result in sacral nerves lesions and bladder or/and intestinal malfunctioning. The aim of this work is to show a clinical case of difficult diagnosis since the fracture was not caused by one violent trauma but by many repeated ones, thus generating doubts at the time of reaching a diagnosis; and to review the literature.